2020
DOI: 10.1590/1678-5150-pvb-6498
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for a field diagnosis of abamectin poisoning in calves

Abstract: An approach for the diagnosis of an abamectin outbreak in calves in the field is described and discussed. In a Midwestern Brazilian property, nine out of a 52 newborn calves were affected and died, making up for morbidity, mortality, and lethality ratios of 17.3%, 17.3%, and 100%, respectively. Major clinical signs included tremors in various muscle groups, inability to stand, and difficult, wheezing breathing. Each affected calf had been treated subcutaneously with abamectin (0.4mg/kg/body weight). No lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Various studies have also indicated the avermectins to have toxic effects on animals [ 26 , 27 , 28 , 29 ]. For example, collie dogs experiencing severe illness presented to the clinic were found to be suffering from ivermectin toxicity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have also indicated the avermectins to have toxic effects on animals [ 26 , 27 , 28 , 29 ]. For example, collie dogs experiencing severe illness presented to the clinic were found to be suffering from ivermectin toxicity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrocyclic lactones promote the inhibitory action of the GABA neurotransmitter, which may lead to generalized muscle hypotonia and cause the death of intoxicated animals. Most animals recover with or without supportive treatment, and lethality ranges from 50-100% (Riet-Correa 2007, Guizelini et al 2020). Considering the weight of the animals (150kg), the therapeutic dose of doramectin indicated would be 3ml; however, the bovines received a dosage compatible with animals weighing 250kg, 1.6 times more than the recommended dose.…”
Section: Discussionmentioning
confidence: 99%
“…The varied and nonspecific clinical signs and the absence of pathological findings make the diagnosis of macrocyclic lactone intoxication a challenge (Guizelini et al 2020). The association of the history of overdose with the clinical course and the absence of gross and microscopic lesions are decisive to the diagnosis of the intoxication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations